Ribosomal DNA magnification in Saccharomyces cerevisiae. - Kaback, D B (1978)
Strains monosomic for chromosome I of Saccharomyces cerevisiae contain 25 to 35% fewer rRNA genes than do normal diploid strains. When these strains are repeatedly subcultured, colonies are isolated that have magnified their number of rRNA genes to the diploid amount while remaining monosomic for chromosome I. We have determined the amount of DNA complementary to rRNA in viable haploid spores derived from a magnified monosomic strain. Some of these haploids contained 24 to 48% more rRNA genes than a normal euploid strain. These extra genes may be responsible for the increased number of rRNA genes in the strain monosomic for chromosome I. Genetic analysis of the haploids containing extra rRNA genes suggested that these genes are linked to chromosomal DNA and are heterozygous. They were not closely linked to any centromere and were not located on chromosome I. Furthermore, all the DNA complementary to rRNA in one of these haploid strains with magnified rRNA genes sedimented at a chromosomal molecular weight, consistent with chromosomal linkage. In addition, several new mutations mapping on chromosome I were used to show that ribosomal DNA magnification was not due to a chromosome I duplication.